Mycobacterium chelonae empyema with bronchopleural fistula in an immunocompetent patient - Wali Siraj (Annals of Thoracic Medicine, 2009)
Mycobacterium chelonae is one of the rapidly growing mycobacteria that rarely cause lung disease . M chelonae more commonly causes skin and soft tissue infections primarily in immunosuppressed individuals. Thoracic empyema caused by rapidly growing mycobacteria and complicated with bronchopleural fistula is rarely reported, especially in immunocompetent patients. In this article we report the first immunocompetent Arabian patient presented with M chelonae- related empyema with bronchopleural fistula which mimics, clinically and radiologically, empyema caused by Mycobacterium tuberculosis.